High susceptibility and low resistance allele frequency of Chrysodeixis includens (Lepidoptera: Noctuidae) field populations to Cry1Ac in Brazil. - YANO, S. A. C. (2015)
BACKGROUND: The soybean looper (SBL), Chrysodeixis includens (Walker), is one of the most important soybean pests in Brazil. MON 87701 × MON 89788 soybean expressing Cry1Ac has been recently deployed in Brazil, providing high levels of control against the primary lepidopteran pests. To support insect resistance management (IRM) programs, the baseline susceptibility of SBL to Cry1Ac was assessed and resistance allele frequency was estimated based on an F2 screen. RESULTS: The toxicity (LC50 ) of Cry1Ac ranged from 0.39 to 2.01 µg·ml-1 of diet among all SBL field populations collected from crop seasons 2008/09 to 2012/13, which indicated approximately 5-fold variation. Cry1Ac diagnostic concentrations of 5.6 and 18 µg·ml-1 of diet were established for monitoring purposes, and no shift in mortality has been observed. A total of 626 F2 family lines derived from SBL collected from locations across Brazil during crop season 2014/15 were screened for the presence of Cry1Ac resistance alleles. None of the 626 families survived on MON 87701 × MON 89788 soybean leaf tissue (joint frequency = 0.0004). CONCLUSIONS: SBL showed high susceptibility and low resistance allele frequency to Cry1Ac across the main soybean-producing regions in Brazil. These findings meet important criteria for effective IRM strategy.